The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s00198-010-1409-9
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse idiopathic skeletal hyperostosis (DISH): relation to vertebral fractures and bone density

Abstract: SummaryRadiographs and spinal bone mineral density (BMD) were evaluated from 342 elderly men regarding possible effects of diffuse idiopathic skeletal hyperostosis (DISH) on vertebral fractures and densitometry measurements. Prevalent vertebral fractures were more frequent among men with DISH compared to men with no DISH even after fracture prevalence was adjusted for BMD. Paravertebral calcifications should be considered in patients with DISH when interpreting BMD measurements because both dual X-ray absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 30 publications
1
69
0
3
Order By: Relevance
“…A recent study comparing DXA and QCT in older men with diffuse idiopathic skeletal hyperostosis demonstrated that QCT was better suited to differentiate men with and without vertebral fractures [47].…”
Section: Bone Densitometrymentioning
confidence: 99%
“…A recent study comparing DXA and QCT in older men with diffuse idiopathic skeletal hyperostosis demonstrated that QCT was better suited to differentiate men with and without vertebral fractures [47].…”
Section: Bone Densitometrymentioning
confidence: 99%
“…(7) DISH often manifests as back pain associated with limited range of spinal motion, but can progress to the extent that lesions interfere with neighboring structures, including compression of the spinal cord and nerve roots. (8,9) Lesions in DISH can also cause dysphagia, (10) and DISH is associated with increased susceptibility to spinal fractures (11) and postsurgical heterotopic ossifications. (12) Correlative studies have associated obesity, hypertension, diabetes mellitus, hyperinsulinemia, dyslipidemia, elevated growth hormone levels, elevated insulin-like growth factor-1, and hyperuricemia with DISH.…”
Section: J Jbmrmentioning
confidence: 99%
“…The risk of spinal injury is compounded by alteration in bone metabolism that accompanies both of these conditions, although with some differences. Increased prevalence of vertebral fractures is seen in patients with AS with diminished relative bone mineral density (11) with similar reports of increased prevalence of vertebral fractures in patients with DISH, although paradoxically with increased bone mineral density on conventional testing (5).…”
mentioning
confidence: 55%